Peningkatan Kreativitas Dan Hasil Belajar IPA Melalui Model Pembelajaran Inkuiri Pada Siswa Kelas V SD Negeri Poleng I Tahun Ajaran 2015/2016 - Adi Susanto, Nova, Dra. Risminawati, M.Pd (2016)
This research applying inquiry learning model that aims to: 1) improve the creativity of fifth grade students of SD Negeri Poleng 1 year 2015/2016, 2) improve learning outcomes Natural Sciences in Class V SD Negeri Poleng 1 year 2015/2016. This type of research is a classroom action research. The research subject teacher and fifth grade students of SD Negeri Poleng 1 totaling 20 children.The technique of collecting data through observation, testing, documentation, and interviews. Data analysis technique used is interactive analysis starts from data reduction, data presentation and then draw conclusions. This study shows that the model of inquiry learning can enhance students' creativity. Increased student creativity can be seen from the increasing creativity aspects of the pre-cycle is 17% then the cycle 1 reached 31%, while in the second cycle aspects of student creativity can be increased to 85%. Inquiry learning model can improve learning outcomes IPA. This is evident from the pre cycle of 25% (5 students completed) then the first cycle at 50% (10 students completed) Cycle II to 80% (16 students completed). The conclusion of this study were: 1) model of inquiry learning can enhance students' creativity in science learning Poleng class V SD Negeri 1 school year 2015/2016, 2) model of inquiry learning can improve learning outcomes Elementary School fifth grade science Poleng 1 academic year 2015 / 2016 Keywords: Inquiry, Creativity, and Learning Outcomes.